Exsplorasi Etnomatematika pada Materi Geometri dan Barisan melalui Permainan Kelereng dan Petak Umpet di Kelas VII SMP Bhakti Mulya - Garda Brendaru Berlin; Deni Efendi; Dwi Desmayanasari (Departement of Mathematics Education, 2024)
This research was carried out with the aim of knowing the arithmetic sequences and sequence patterns found in the game of marbles and hide and seek at Bhakti Mulya Middle School. This type of research is qualitative research with an interactive qualitative design, namely ethnographic field studies in collecting data directly from the natural environment. The research was conducted in 3 meetings. The data techniques used in this research are observation, interviews, and documentation which are analyzed using the interactive model data analysis technique proposed by Miles and Huberman, namely data, data reduction, data display, and data. taking. The results of the research show that: (1) there is a pattern of counting rows and arithmetic sequences in the game of marbles and hide and seek at Bhakti Mulya Middle School where the application of these concepts is applied naturally without studying the mathematical concepts of the Bhakti Mulya Middle School community, (2) there is a meaning in the use of kandaure in every Toraja community activities include ramba solo' activities which are used as decorations in traditional ceremonies, decorations in the Bhakti Mulya Middle School mortuary, complementary accessories for Toraja traditional clothing at death ceremonies, and tuka signs used as wedding ceremony decorations and complementary accessories for Toraja traditional clothing. at weddings or dances, (3) there is a connection between mathematics learning and arithmetic sequence patterns in marbles and hide-and-seek games at Bhakti Mulya Middle School, especially in the arithmetic sequences and series material studied at school. Thus, it can be ignored that the counting row pattern and series of marble and hide and seek games at Bhakti Mulya Middle School have a connection with mathematics learning and also have useful meaning in every activity of the Bhakti Mulya Middle School community.